Strategi Pengembangan Objek Wisata Museum Kota Tanjung Pinang Sultan Sulaiman Badrul Alamsyah - Devid Trinaldo Simatupang (JURNAL AS-SAID, 2022)
Tanjungpinang City itself has potential in the tourism sector. Tanjungpinang city has historical heritage that is recorded in history books. These historical relics are very interesting to be visited. Strategy is very important for the development of an organization/company in order to achieve goals, both short-term and long-term goals. Analysis in strategy development is based on the dimensions of the strategy used, namely Objectives, Policies and Programs.